Economic and environmental impacts of raising revenues for climate finance from public sources. (21st April 2021) - Böhringer, Christoph; Schneider, Jan; Springmann, Marco
ABSTRACT: In response to anthropogenic climate change, developed countries have committed themselves to raising 100 billion USD a year from 2020 onwards to address the needs of developing countries. In this paper, we investigate the economic consequences and CO2 emission impacts of three options for raising climate funds from public sources in developed countries: (i) CO2 emissions pricing, (ii) an electricity consumption tax, and (iii) the removal of fossil fuel subsidies. Using computable general equilibrium analysis, we find that these three options not only induce very different global costs to raise given amounts of climate funds, but also have quite diverging implications for the cost incidence between developed and developing countries. Likewise, the global CO2 emission impacts of alternative fund-raising policies differ significantly. Key policy insights CO2 emission pricing and a tax on electricity consumption in developed countries shift substantial shares of the cost burden for raising climate finance to developing countries, while the removal of fossil fuel subsidies in developed countries leads to welfare gains for developing countries. While CO2 pricing and a tax on electricity consumption lead to positive carbon leakage, i.e. increased emissions in developing countries, the removal of fossil fuel subsidies incentivizes decarbonization of developing economies through higher prices for fossil fuels. From a global cost-effectiveness perspective the removal of subsidies is the least attractive option, but it gains in attractiveness for a policy portfolio when taking into account the cost incidence between developed and developing countries, and also the impact on CO2 emissions in developing countries.